PERFORMANCE MEASUREMENT ANALYSIS RELATED TO CHANGES IN NOMENCLATURE AT THE ANIMAL, FISH, AND PLANT QUARANTINE OFFICE OF THE RIAU ISLANDS USING THE BALANCE SCORECARD (BSC) MODEL - Liza Rickiany; Ngaliman; Sarmini (CV. Radja Publika, 2025)
Nomenclature changes in public institutions often create significant challenges for organizational effectiveness, particularly in aligning tasks, redistributing human resources, and maintaining the quality of public services. This condition is also experienced by the Animal, Fish, and Plant Quarantine Office of Riau Islands, which faces structural complexities following institutional restructuring. This study aims to analyze the organizational performance after the nomenclature change using the Balanced Scorecard (BSC) approach. The research employed a qualitative method with in-depth interviews involving key informants directly engaged in management and quarantine services. Data were analyzed through thematic coding with the assistance of NVivo software, allowing each BSC perspective to be comprehensively examined. The findings reveal that from the financial perspective, budget management is relatively efficient but still requires optimization in transparency and accountability. From the customer perspective, there is an increase in satisfaction and trust in quarantine services, showing that restructuring has strengthened public service delivery. The internal process perspective indicates positive adaptation to the new structure, although challenges remain in terms of uneven human resource distribution and regulatory adjustments. Meanwhile, the learning and growth perspective underscores the importance of continuous staff development and the integration of information technology to build an adaptive work culture. Overall, the Balanced Scorecard proves to be an effective evaluation instrument for assessing public sector performance, while also providing policy implications in terms of strengthening financial governance, redistributing human resources, and modernizing internal processes to enhance efficiency, accountability, and public service quality.